Forced Efforts in the Execution of Decisions of the State Administrative Court - Pradana, Arigo Henry; Amarini, Indriati; Kartini, Ika Ariani (UMPurwokerto Law Review, 2021)
The State Administrative Court is the executor of judicial power assigned to examine, decide and resolve State Administrative disputes. This research has two problems: forced attempts to execute the state administrative court’s verdict and the obstacles in implementing these forced attempts. The research method is normative legal research called normative juridical research or doctrinal research that looks at the law’s objectives, the values of justice, the validity of the rule of law, the law’s concept, and legal norms. The implementation of forced efforts against The State Administrative Court decision under Article 116 paragraph (4) of Law Number 51 of 2009 can be applied in executing the State Administrative Court’s decision. Institution for forced efforts consists of forced money, administrative sanctions, and announcements/publications important in the effort to force lies in State Administrative Officials’ awareness to voluntarily comply with the State Administrative Court’s decisions. Keywords: forced effort; execution, court decision Â